Correlation Between HbA1c and Albuminuria in Type 2 Diabetes Mellitus - Jesika Merlin; Pusparini Pusparini (Majalah Kedokteran Bandung, 2020)
In patients with type 2 diabetes mellitus (Type 2 DM), glycemic control plays an essential role in reducing macro- and microvascular complications. The earliest marker for diabetic nephropathy is the presence of albuminuria. Meanwhile, HbA1c  has been recognized as a marker of glycemic control in the blood. This study aimed to identify the correlation between HbA1c and albuminuria in type 2 DM. This was a cross-sectional study involving 100 patients with type 2 DM aged 40–70 years visiting Dr. Soetomo Hospital, Surabaya, Indonesia. Secondary data from medical records of type 2 DM patients undergoing HbA1c and albuminuria examinations from January to December 2015 were used. The mean age of subjects was 55.4 ±8.7 years, with the majority (55%) being of female gender. The mean HbA1c concentration was 9.8±2.4%. Most subjects (83%) had an HbA1c level of ≥7 %. Albuminuria was found in the majority of the subjects (78%), where 33% of them had positive  1 albuminuria. The Spearman correlation test showed a positive strong significant correlation between HbA1c and albuminuria, with r=0.865 and p<0.001. Thus, it can be concluded that there is a significant correlation between HbA1c and albuminuria in type 2 DM.Korelasi HbA1c dan Albuminuria pada Diabetes Melitus Tipe 2 Pada penderita diabetes melitus tipe 2 (DM tipe 2), kontrol glikemik memegang peranan penting untuk menurunkan komplikasi makrovaskular dan mikrovaskular. Petanda awal terjadinya nefropati diabetik adalah adanya albuminuria. HBA1c merupakan petanda untuk mengetahui kontrol glikemik didalam darah. Tujuan penelitian ini untuk mengetahui korelasi antara HbA1c dengan albuminuria pada  DM tipe 2. Penelitian ini menggunakan desain potong lintang, mengikutsertakan 100 penderita DM tipe 2 berusia 40–70 tahun di Rumah Sakit Dr. Soetomo Surabaya. Data yang digunakan adalah data sekunder dari rekam medis penderita DM tipe 2 yang melakukan pemeriksaan HbA1c dan albuminuria pada bulan Januari 2015 sampai dengan Desember 2015. Rerata usia subjek adalah 55,47±8,7 tahun dengan subjek terbanyak berjenis kelamin perempuan (55%). Rerata kadar HbA1c berkisar 9,8±2,4 %. Sebagian besar subjek mempunyai kadar HbA1c ≥7 % yaitu 83%. Albuminuria dijumpai pada sebagian besar subjek yaitu 78% dan sebagian besar subjek mempunyai albuminuria positif 1, yaitu 33 %. Hasil uji korelasi Spearman menunjukkan terdapat korelasi positif kuat yang bermakna antara HbA1c dengan albuminuria dengan nilai r=0,865 dan p<0,001. Dengan demikian, dapat disimpulkan terdapat korelasi yang bermakna antara HbA1c dan albuminuria pada DM tipe 2.